Serum metabolomics reveals that arsenic exposure disrupted lipid and amino acid metabolism in rats: a step forward in understanding chronic arsenic toxicity1. Issue 3 (11th March 2015) - Wang, Xiaoxue; Mu, Xiaoli; Zhang, Jie; Huang, Qingyu; Alamdar, Ambreen; Tian, Meiping; Liu, Liangpo; Shen, Heqing
<x xml:space="preserve">Abstract</x> Chronic arsenic exposure induces metabolome disruption in rat.